Pengaruh Akuntansi Pertanggungjawaban pada Penyaluran Dana Zakat Produktif - Susiyati, Tri (Jurnal Trikonomika, 2009)
Nowdays zakat foundation has spread as a temporary foundation or a consumerize expense. Zakat as an economic foundation can manage qualified human resources development professional an comprehensively. Through the productivity of zakat foundation,the moslem. Community has an ability of expert in doing business can develop their business.And of course,we can get it from the professional Amil. In this research, the important subject is Amil Dhompet Dhuafa Bandung, In transforming the productive zakat to the mustahik mostly this research shows us that. There is a significant effect between responsibility and management of zakat in professionally. It can give a prosperous mustahik a positive effect.